Fear, anger, and media-induced trauma during the outbreak of COVID-19 in the Czech Republic - Trnka, Radek; Lorencova, Radmila (Psychological trauma, 2020)
Fear, anger and hopelessness were the most frequent traumatic emotional responses in the general public during the first stage of outbreak of the COVID-19 epidemic in the Czech Republic (N = 1,000). The four most frequent categories of fear were determined: (a) fear of the negative impact on household finances, (b) fear of the negative impact on the household finances of significant others, (c) fear of the unavailability of health care, and (d) fear of an insufficient food supply. The pessimistic communications used by the Czech mass media contributed to intensifying traumatic feelings, fears and psychological distress in the general public during the outbreak of the COVID-19 epidemic. (PsycInfo Database Record (c) 2020 APA, all rights reserved).
Keywords: dospělí; Coronavirus Infections; kontrola infekce; Female; Pessimism; Adult; ženské pohlaví; mladý dospělý; Adolescent; psychické trauma; lidé; pesimismus; Psychological Trauma; psychický distres; koronavirové infekce; optimismus; COVID-19; Aged, 80 and over; Pneumonia, Viral; Fear; virová pneumonie; pandemie; Optimism; strach; Male; Aged; Czech Republic; Young Adult; Česká republika; Infection Control; Psychological Distress; lidé středního věku; Mass Media; senioři nad 80 let; senioři; mužské pohlaví; hromadné sdělovací prostředky; Pandemics; Middle Aged; mladiství; Humans